Implementation of Mine Reclamation Guarantee Based on Government Regulation Number 78 of 2010 Concerning Reclamation and Post-Mining in IKN - Sugiharto, Grisela Mawa Aqilah; Arifudin, Nur; Susanti, Erna (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Reclamation is a critical environmental recovery measure aimed at restoring former mining areas to a sustainable and functional state. This research investigates the role of government supervision and law enforcement in the reclamation of ex-mining land within the development zone of Indonesia’s new National Capital (IKN), located across North Penajam Paser and Kutai Kartanegara Regencies in East Kalimantan. As the IKN project represents a large-scale transformation of land use, the study focuses on how regulatory oversight and enforcement influence the effectiveness of reclamation efforts. Using a qualitative descriptive method, the study collects data through document analysis, field observations, and interviews with local government officials, environmental agencies, and stakeholders in the mining and reclamation sectors. The findings reveal that while regulatory frameworks for reclamation exist, challenges remain in implementation due to overlapping authority, limited monitoring resources, and weak enforcement of legal obligations by mining companies. Additionally, many ex-mining lands remain unproductive and pose environmental risks due to insufficient reclamation. The study emphasizes the need for a more integrated and accountable supervision system, increased inter-agency coordination, and stricter enforcement mechanisms to ensure that reclamation aligns with sustainable development goals. The implications of this research highlight the importance of legal compliance and government leadership in managing environmental risks in areas designated for national development projects.